The importance of acute-phase proteins as markers in cancers - Zegarska, Paulina; Markowska, Urszula; Płoszaj, Małgorzata (Medical Studies/Studia Medyczne, 2021)
Acute-phase proteins (APPs) form a group of heterogeneous proteins whose synthesis takes place in the liver. This involves mediators such as cytokines and constitutes a response to acute inflammations, bacterial infections, tumours, and autoimmune diseases. C-reactive protein is among the most important APPs. It participates in cancerous processes, especially in colon and rectal cancer. Another APP is haptoglobin. This glycoprotein prevents iron loss and kidney damage, and is associated with diagnostic neoplastic progression connected with fucosylation. Fucoso–haptoglobin is a highly effective marker for prognosis because an increased concentration of this complex is indicative of the distant metastases amount. Another APP is acidic -glycoprotein (AGP), which increases to a serious level during acute inflammations and tumour-promoting processes. Its protective role involves platelet aggregation inhibition and chemotactic activity. The purpose of this study was to review the role of selected acute phase proteins in cancer promotion and progression.